1999
DOI: 10.1016/s0735-1097(99)00063-7
|View full text |Cite
|
Sign up to set email alerts
|

Volume overload hypertrophy of the newborn heart slows the maturation of enzymes involved in the regulation of fatty acid metabolism

Abstract: Early onset LV volume overload with hypertrophy results in a delay in the normal maturation of fatty acid oxidation in the newborn heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 24 publications
3
35
0
Order By: Relevance
“…Therefore, whether the expressional changes observed can be extrapolated to the left ventricle, and as such, whether these changes occur at the whole heart level remains unknown. Our previous report examining the maturation of fatty acid oxidation in the newborn pig heart (21 d of age) reveals that there is no difference in the content of malonyl CoA, or the activities of either ACC or AMPK in the setting of volume overload hypertrophy between the right and left ventricles (17). However, there are currently no published reports characterizing possible differences in the regional expression of MCD, ACC, and AMPK between the right and left ventricles, as such this issue remains to be addressed.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, whether the expressional changes observed can be extrapolated to the left ventricle, and as such, whether these changes occur at the whole heart level remains unknown. Our previous report examining the maturation of fatty acid oxidation in the newborn pig heart (21 d of age) reveals that there is no difference in the content of malonyl CoA, or the activities of either ACC or AMPK in the setting of volume overload hypertrophy between the right and left ventricles (17). However, there are currently no published reports characterizing possible differences in the regional expression of MCD, ACC, and AMPK between the right and left ventricles, as such this issue remains to be addressed.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in ACC activity have been demonstrated to contribute to the maturation of fatty acid oxidation in hearts obtained from both newborn rabbits (1 and 7 d of age) (9,17,28), as well as hearts obtained from newborn pigs (14 d of age) (9,17,28). As we did not observe any age-dependent alteration in the phosphorylation of ACC (indicative of ACC inhibition), the data in this study suggests that in the newborn human heart the synthesis of malonyl CoA and maturation of fatty acid oxidation is not regulated by ACC activity, but is rather regulated by the extent of ACC expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While adult cardiac hypertrophy results in a fetal-like metabolic phenotype (38), the effect(s) of hypertrophy on the neonatal heart, in the midst of a fetal-to-adult transition, is unclear. We previously showed that newborn cardiac hypertrophy in pig hearts delays the maturation of key fatty acid oxidation enzymes (20). However, the effects of hypertrophy on energy metabolic rates in the neonatal heart have not been directly determined.…”
mentioning
confidence: 99%